2016
DOI: 10.1016/j.jcms.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

ENPP1 and ESR1 genotypes influence temporomandibular disorders development and surgical treatment response in dentofacial deformities

Abstract: Dentofacial deformities are dys-morpho-functional disorders involving the temporomandibular joints (TMJ). Many authors have report a TMJ improvement in dysfunctional subjects with malocclusion after orthodontic or combined orthodontic and surgical treatment particularly for the relief of pain. In particular, few studies have highlighted the demographic and clinical predictors of response to surgical treatment. To date, no genetic factor has yet been identified as a predictor of response to surgical treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 83 publications
1
26
0
1
Order By: Relevance
“…10,18 We also found differences in gene expression for PITX1 and PITX2 between left and right masseter muscle in asymmetry. 4 In this study, we explore associations between these genes and subclassifications of asymmetry.…”
Section: Introductionsupporting
confidence: 51%
See 4 more Smart Citations
“…10,18 We also found differences in gene expression for PITX1 and PITX2 between left and right masseter muscle in asymmetry. 4 In this study, we explore associations between these genes and subclassifications of asymmetry.…”
Section: Introductionsupporting
confidence: 51%
“…49 We have recently reported that rs858339 has a significant association with the occurrence of preoperative TMD in our patient population. 18 ENPP1 rs858339 TT genotype associated with pretreatment absence of TMD and the AT genotype as a pretreatment risk factor for presence of TMD as determined by JPF scores. 18 In this study rs858399 has strong statistical association with the TMD diagnoses of disc displacement with reduction, masticatory muscle myalgia or arthralgia, further confirming its role in etiology (Table 5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations